Implementation of Business Process Reengineering during New Normal in Dinamika University Library - Ayouvi Poerna Wardhanie; Tan Amelia (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2022)
This research aims to find out how the implementation of business process reengineering occurred in the Dinamika University library during the new normal era. The method uses an exploratory approach by conducting in-depth interviews with key informants, the head of the library division, and the primary informants are library staff. This research will stop if the informants interviewed by the researcher provide the same information or the answers are no longer varied. In this study, the data collection uses triangulation techniques that combine documentation studies, participant observation, and in-depth interviews. The findings of this study are the breakthrough in making the Library Online Services Application and the Dynamics of Box of Sterilization to sterilize a collection of books that have been borrowed, routinely promoted through Instagram, and developing an independent upload system.